2017
DOI: 10.1186/s12893-017-0304-0
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for lymph node metastasis in early gastric cancer patients: Report from Eastern Europe country– Lithuania

Abstract: BackgroundCurrent risk factors for lymph node metastasis in early gastric cancer have been primarily determined in Asian countries; however their applicability to Western nations is under discussion. The aim of our study was to identify risk factors associated with lymph node metastasis in Western cohort patients from the Eastern European country - Lithuania.MethodsA total of 218 patients who underwent open gastrectomy for early gastric cancer were included in this retrospective study. After histolopathologica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
24
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 31 publications
3
24
0
1
Order By: Relevance
“…The location of tumor was categorized as cardia, corpus/fundus, and antrum/angularis/pylorus. Tumor size which means the maximum diameter of tumor was recorded with continuous variable, then converted to a classification variable with the threshold value < 2.20 cm and ≥ 2.20 cm, analyzed by optimal binning, which was consistent with previous studies [14,16]. The macroscopic feature was classified into three groups: elevated type (types I and IIa), flat type (type IIb), or depressed type (types IIc and III).…”
Section: Clinicopathologic Characteristicsmentioning
confidence: 91%
See 1 more Smart Citation
“…The location of tumor was categorized as cardia, corpus/fundus, and antrum/angularis/pylorus. Tumor size which means the maximum diameter of tumor was recorded with continuous variable, then converted to a classification variable with the threshold value < 2.20 cm and ≥ 2.20 cm, analyzed by optimal binning, which was consistent with previous studies [14,16]. The macroscopic feature was classified into three groups: elevated type (types I and IIa), flat type (type IIb), or depressed type (types IIc and III).…”
Section: Clinicopathologic Characteristicsmentioning
confidence: 91%
“…But the probability of LNM is still evaluated by the general guidelines and surgeon's experience without quantified standards in clinical practice nowadays. Although several studies have tried to explore the risk factors of LNM in EGC, most items involved, such as lymphovascular invasion and depth of tumor invasion, were unavailable preoperatively [13,14]. The comprehensive analysis of gastroscopic findings, tumor markers, and radiology images, rather than individual analyses, is the most promising way to improve clinical management [15].…”
Section: Introductionmentioning
confidence: 99%
“…Shen L et al [18] reported that LNM was observed in 12.20% of EGC patients. In another study [22], LNM was reported in 19.7% of EGC cases. The reported rates range from 5.7-20% of patients [23][24][25][26][27][28].…”
Section: Discussionmentioning
confidence: 85%
“…However, good outcomes in the follow-up group according to DSS and recurrence rates should be treated carefully due to different background characteristics of the study groups. Some major risk factors for LNM (lymphatic invasion or deeper submucosal invasion) were significantly more frequent in the additional radical surgery group [ 18 , 19 ], and these differences may influence the study results. Furthermore, Suzuki et al [ 20 ] recently published results from the similar study and showed a clear superiority of additional surgery after non-curative ESD compared to follow-up.…”
Section: Discussionmentioning
confidence: 99%